(3GdTQM GdUZjQ Ydi GdeNJUQ GdfGaYs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3eMeO Hf ESeGYjd GdQVhjs)
(3ChdgG (B:s
(3ChdgG(B: (3cJGH GddbWI, hgj HVe GddGe haJM GdbGa hSchfgG, GSe ddeGd GdedbhW Ydi eG fbd Yf LeGYI ef Cgd GddZI cGdCUeYj hGHf GdCYQGHj hGdaQGAs
(3BNQgG (B:s
(3BNQgG(B: (3HGdLfGjI eef jYbd Yfg Ydi GdCPi aMSH HdG NdGa aj TjA ef Pdc CLOg ddCUd eY GNJUGU eG Od Ydi VeGf GdYGbdI ef GdaJhi hGdQhGjI HLfGjI GdBOej Ydi eKdg NWCs
(3efbhdI ef fSNI GdeDda, CJe GdeDda JCdjagG SfI (B1192(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 17s
(3GdPQjYI, L (B13: 218s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis